The Use of Marine Mushroom Extract (Nodulisporium sp.) as Feed Additive in the Ration of Native Chickens on Protein Utilisation Ratio - Br Surbakti, MO.; Nurhayati; Nelwida (Talenta Publisher, 2023)
Feed plays an important role in the growth process of native chickens. This research aims to determine the effect of using marine fungi extract (Nodulispolium sp.) as a feed additive in native chicken rations on the protein utilization ratio. This research was a collaboration between the IPB University and Jambi University which used 180 unsexing DOC native chickens and marine fungi extract. The design used was a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications. The treatments were P0 = Basal Ration (control), P1 = P0 + 1 ml marine fungi extract/kg, P2 = P0 + 2 ml marine fungi extract/kg, P3 = P0 + 3 ml marine fungi extract/kg and P4 = P0 + 4 ml marine fungi extract/kg. The variables observed included dry matter consumption, crude protein consumption, body weight gain and protein utilization ratio. Data were analyzed using analysis of variance (ANOVA) and the differences between treatments, adding were tested using Duncan's Multiple Range Test. The results of analysis of variance showed that the use of marine fungi extract as a feed additive in rations up to 4 ml/kg ration had no significant effect (P>0.05) on dry matter consumption, crude protein consumption, body weight gain and protein utilization ratio. It can be concluded that the use of marine fungi extract as a feed additive in rations up to 4 ml/kg has not been able to increase the protein ratio chickens